3D printing with Autodesk 123D?, Tinkercad?, and Makerbot? - Cline, Lydia Sloan (McGraw-Hill's AccessEngineering., 2015)
Are you ready to join the new industrial revolution? Cline reveals how to turn your ideas into physical products that you can use or sell!.